Medical expertise in cervical spinal injuries: Medicinsko izvedenstvo pri poškodbah vratne hrbtenice - Kadiš, Peter (Acta Medico-Biotechnica, 2021)
Cervical spinal injury is one of the most frequent injuries in traffic accidents and is therefore often dealt with in the courts in criminal and civil proceedings. To form an expert opinion on cervical spinal injuries, it is, primarily, necessary to acquire complete medical records of the injured person, including original X-ray images and other test results. To determine the permanent consequences of injuries or previous cervical spinal impairment, it is necessary for the injured person to undergo a medical examination. Especially in mild cases of whiplash injury, it is necessary to acquire appropriate data on the mechanism of injury and biomechanical parameters which, for traffic accidents, can be obtained from experts in the field of traffic accident research.
Keywords: injuries; cervical spine; traffic accidents; expert opinion